Features of atmospheric pressure discharges with a transverse component of the velocity of gas flow to the current channel - Chernyak, V.Ya.; Iukhymenko, V.V.; Iukhymenko, K.V.; Klochok, N.V.; Kolomiiets, O.V.; Hamazin, D.K.; Chernolutsky, D.L. (Вопросы атомной науки и техники, 2018)
The atmospheric pressure rotating gliding discharge was studied in work. A comparison of a rotating gliding discharge with a discharge in a transverse airflow were made. The clear analogies between rotating gliding discharge and discharge in the transverse airflow, were found during research.